Vegetation Inventory in the Kedah Protected Forest Bungalow Blangjerango District, Gayo Lues Regency - Wan fatimah (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
Vegetation inventory research has been carried out (herbs, shrubs, trees) in the protected forest of Kedah Bungalow, Blangjerango District, Gayo Lues Regency, conducted in August to October 2019. This study aims to determine the types of herbal plants, bushes, trees found in the Kedah protected forest Blangjerango Subdistrict of Gayo Lues Regency, the approach used in this study was qualitative, the type of research used exploratory surveys, namely observing in the study area. The study was conducted using the quadratic method (plot), with plot area for herbs 2m x 2m, for bushes 5m x 5m and for trees 10m x 10m. Data on herbaceous vegetation, shrubs, trees were analyzed descriptively, data analyzed in the form of the identity of herbaceous plants, shrubs, trees found at the research location. The results obtained were 34 species of herbs from 20 families, Asteraceae namely 10 species, followed by Poaceae 3 species, Araceae 3 species, Fabaceae 2 species, Euphorbiaceae 2 species, Amaranthaceae 2 species, and 1 species each from the family Portulaceae, Mimosaceae, Commelinaceae , Rubiaceae, Marsileaceae, Umbelliferaceae, Solanaceae, Piperaceae, Plantanginaceae, Cleomaceae, Araliaceae, Convolvulaceae. 32 shrub species from 18 families, Fabaceae 4 species, Malvaceae 4 species, Asteraceae 3 species, Verbenaceae 2 species, Melastomataceae 2 species, Arecaceae 2 species, Piperaceae 2 species, Malvaceae 2 species, Solanaceae 2 species, and 1 species each familia Onagraceae, Oxalidaceae, Rubiaceae, Apocynaceae, Euphorbiaceae, Petiveriaceae, Lamiaceae, Aspleniaceae. 45 species of trees from 23 families. Fabaceae 7 species, Malvaceae 4 species, Lauraceae 4 species, Meliaceae 3 species, Moraceae 3 species, Dipterocarpaceae 2 species, Sapindaceae 2 species, Myrtaceae 2 species, Rubiaceae 2 species, Anacardiaceae 2 species, Araceae 2 species, and 1 species each from the family Lamiaceae, Burseracea, Combretaceae, Euphorbiaceae, Sapotaceae, Annonaceae, Santalaceae, Phyllanthaceae, Urticaceae, Elaeocarpaceae, Myristicaceae, Bombacaceae.